Introduction to electrodynamics - Capri, A. Z.; Panat, P. V. (New Delhi: Narosa Publishing House, 2002)
Aimed at removing the difficulties faced by an average student, this book has grown out of long teaching experience of the authors. Beginning with vector calculus, boundary value problems of electrostatics and magnetostatics are thoroughly discussed. Radiation, relativity and radiation from an accelerated change with emphasis on physics are carefully presented. Advanced topics like Lorentz Group, Green's function and motion of changed particles in electric and magnetic field are treated with care.
Appendix A, 454-459p.; Index 460-465p.
Keywords: Electrodynamics; Physics